Terveyshistoria Näkökulmia ja lähestymistapoja keskiajalta nykypäivään - Kananoja, Kalle (Historiallisia Tutkimuksia, 2022)
This book deals with approaches, sources, and methods in health history from the middle ages to the twentieth century. Individual chapters demonstrate how historians of medicine and health choose their methodological approaches and form interpretations from primary sources. They discuss the practices of writing and show how obstacles in the research process can be overcome. Practical examples of source materials, used methods and research challenges give tools to students for carrying out projects independently and help them to understand different possibilities in the field of health history. In this book, history of health includes but is not limited to medical science. Emphasising medical pluralism, it places (public) health in a cultural and social field encompassing official and unofficial practitioners, medical institutions, and patients. Individual case studies highlight themes in Finnish, European, and African history.